Activated T cells in an animal model of allergic conjunctivitis. Issue 8 (August 1993) - Carreras, I; Carreras, B; McGrath, L; Rice, A; Easty, D L
Abstract : The aim of this study has been to determine whether the presence of lymphocytic infiltrates observed in the histology of ocular allergic conditions in humans or in the late phase of ocular anaphylactic reactions in experimental animals is a non-specific event dependent only on the degranulation of mast cells, or is conditioned by a specific response to antigen. With this in mind, responses to antigen and to a non-immunological mast cell degranulator (compound 48/80) were compared in an experimental model of allergic conjunctivitis. Rats were sensitised to ovalbumin and challenged topically in the left conjunctival sac either with ovalbumin or compound 48/80. The presence of T cells and activated T cells in the infiltrate was studied by immunohistochemical staining on conjunctival tissue obtained at 4, 24, and 48 hours after challenge. Ovalbumin sensitised and challenged rats showed increased numbers of T cells in the conjunctival infiltrate, statistically significant when compared with compound 48/80 challenged rats at 48 hours and with controls at 4, 24, and 48 hours. The number of T cells was significantly higher in compound 48/80 challenged rats only at 48 hours when compared with controls. As for the number of activated T cells, only ovalbumin sensitised and challenged rats showed significantly increased levels of these cells compared with both sensitised animals challenged with compound 48/80 and controls at 4 and 24 hours after challenge. These results suggest that the infiltration of the conjunctiva by activated T lymphocytes is, at least in part, dependent on a specific response to antigen.